CHD7 and 53BP1 regulate distinct pathways for the re-ligation of DNA double-strand breaks - Magdalena B. Rother (Nature Portfolio, 2020)
Chromatin is dynamically remodeled in response to DNA damage in favour of repair. Here the authors reveal how the chromatin remodeler CHD7 and chromatin binding protein 53BP1 regulate distinct DNA repair pathways.